Perancangan Sistem Informasi Perpustakaan Digital untuk Siswa Yaspend IKAL BULOG SUMUT - Muzammil, Abdullah Umar; Muhammad, Mar’ie Aqil Reyhan; Akbar, Dwi Hafizah; Amanda , Bazlina Dini; Ikhwan, Ali (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The school library at Yaspend Ikal Bulog Sumut plays a vital role in providing various reading materials to support students' learning activities. However, based on observations and interviews with the librarian, it was found that library management is still conducted manually, such as recording book borrowings and returns, which often leads to issues, including data loss. This study aims to design a web-based library information system that facilitates easy access and digital management of reading materials. The system was designed using the Scrum methodology and includes features that allow for collection searches, borrowing data management, and more flexible access to learning resources. The implementation of the system showed satisfactory results in supporting modern library management needs, with the potential to enhance students' accessibility to various learning materials in a practical manner.